Metallothionein‐I/II expression associates with the astrocyte DNA damage response and not Alzheimer‐type pathology in the aging brain. Issue 11 (10th August 2018) - Waller, Rachel; Murphy, Mark; Garwood, Claire J; Jennings, Luke; Heath, Paul R; Chambers, Annabelle; Matthews, Fiona E; Brayne, Carol; Ince, Paul G; Wharton, Stephen B; Simpson, Julie E; ,
Abstract: Oxidative stress and oxidative DNA damage are early features of mild cognitive impairment and Alzheimer's disease (AD), occurring before the formation of classical AD neuropathology, and resulting from an imbalance between pro‐ and anti‐oxidants. Astrocytes play a major neuroprotective role, producing high levels of anti‐oxidants including metallothionein‐I and ‐II (MT‐I/II). In the present study we characterized the immunoreactive profile of MT‐I/II in the temporal cortex of the Cognitive Function and Ageing Study (CFAS) aging population‐representative neuropathology cohort, and examined H2 O2 ‐modulation of MT transcription by human astrocytes. MT‐I/II is primarily expressed by astrocytes in the aging brain, but is also associated with pyramidal neurons in a small proportion of cases. Astrocyte expression of MT‐I/II does not correlate with Alzheimer‐type pathology (Aβ plaques and neurofibrillary tangles) but does relate to astrocyte oxidative DNA damage ( r s = .312, p = .006) and the astrocyte response to oxidative DNA damage in vivo ( r s = .238, p = .04), and MT gene expression is significantly induced in human astrocytes response to oxidative stress in vitro ( p = .01). In contrast, neuronal MT‐I/II does not relate to oxidative DNA damage or the neuronal DNA damage response, but is significantly higher in cases with high levels of local tangle pathology ( p = .007). As MT‐I/II is neuroprotective against oxidative stress, modulation of MT‐I/II expression is a potential therapeutic target to treat the onset and progression of cognitive impairment. Main Points: MT‐I/II is expressed by astrocytes in the aging brain. MT‐I/II expression does not correlate with Alzheimer pathology but to astrocyte oxidative DNA damage in vivo. In response to oxidative stress MT genes are induced in human astrocytes in vitro.